Spontaneous head movements support accurate horizontal auditory localization in a virtual visual environment - Gulli, Andrea; Fontana, Federico; Orzan, Eva; Aruffo, Alessandro; Muzzi, Enrico (PloS one, 2022)
This study investigates the relationship between auditory localization accuracy in the horizontal plane and the spontaneous translation and rotation of the head in response to an acoustic stimulus from an invisible sound source. Although a number of studies have suggested that localization ability improves with head movements, most of them measured the perceived source elevation and front-back disambiguation. We investigated the contribution of head movements to auditory localization in the anterior horizontal field in normal hearing subjects. A virtual reality scenario was used to conceal visual cues during the test through a head mounted display. In this condition, we found that an active search of the sound origin using head movements is not strictly necessary, yet sufficient for achieving greater sound source localization accuracy. This result may have important implications in the clinical assessment and training of adults and children affected by hearing and motor impairments.